Data on population and community effects for lake bacterioplankton in different seasons - Lindström, Eva S. (Uppsala University, 2017)
This dataset is based on an investigation of the seasonal variation in the importance of dispersal from different sources (mixing, precipitation, surface runoff and sediment resuspension) for lake bacterioplankton community and population dynamics. Two small forest lakes and their dispersal sources were sampled over a period of 10 months

See manuscript "Contribution of different bacterial dispersal sources to lakes: Population and community effects in different seasons" by Comte et al (2017) for further info on data and analytical results.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost, samt manuskriptet "Contribution of different bacterial dispersal sources to lakes: Population and community effects in different seasons" av Comte et al (2017), för information om data och analysresultat.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on population and community effects for lake bacterioplankton in different seasons
Supporting data version 2
Keywords: seasons; årstider; plankton; plankton; Ecology; Ekologi